A balance of Btk and SHIP activation regulates B-cell receptor cluster formation by controlling actin remodeling - Liu, Chaohong (2011)
The activation of the B-cell receptor (BCR), which initiates B-cell activation, is triggered by antigen-induced self-aggregation and clustering of receptors at the cell surface. While antigen-induced actin reorganization is known to be involved in BCR clustering in response to membrane-associated antigen, the underlying mechanism that links actin reorganization to BCR activation remains unknown. Here we show that both the stimulatory Bruton’s tyrosine kinase (Btk) and the inhibitory SH2-containing inositol-5 phosphatase-1 (SHIP-1) are required for efficient BCR self-aggregation. In Btk-deficient B cells, the magnitude of BCR aggregation into clusters and B-cell spreading in response to antigen-tethered lipid bilayer is drastically reduced, compared to that observed in wild type B-cells. In SHIP-1(−/−) B-cells, while surface BCRs aggregate into microclusters, the centripetal movement and growth of BCR clusters are inhibited and B-cell spreading is increased. The persistent BCR microclusters in SHIP(−/−) B-cells exhibit higher levels of signaling than merged BCR clusters. Contrast to the inhibition of actin remodeling in Btk-deficient B-cells, actin polymerization, F-actin accumulation, and WASP phosphorylation are enhanced in SHIP-1(−/−) B-cells in a Btk-dependent manner. Thus, a balance between positive and negative signaling regulates the spatiotemporal organization of the BCR at the cell surface by controlling actin remodeling, which potentially regulates the signal transduction of the BCR. This study suggests a novel feedback loop between BCR signaling and the actin cytoskeleton.